The positive effect of assortment size on purchase likelihood: The moderating influence of decision order1. Issue 4 (14th December 2015) - Gao, Leilei; Simonson, Itamar
Abstract: The effect of assortment size on purchase decisions is an ongoing subject of debate, in light of conflicting findings (Scheibehenne, Greifeneder, & Todd, 2010). The authors show that a key determinant of the effect is the order in which "whether to buy" and "which option to choose" decisions are made. Increasing assortment size has a more positive effect on the likelihood of consumers to make a purchase when the initial decision emphasis is on whether to make a purchase from a given set of options, as opposed to first identifying the best available option in the set. This prediction is based on the proposition that decision order determines how likely consumers are to make trade‐offs between the perceived costs and benefits associated with a large product assortment, and that the benefits are given relatively greater weight when consumers decide first "whether to buy" (rather than "which option to choose"). Two incentive‐compatible studies, using a systematic manipulation of assortment size and decision order, support the prediction.